A Behavioral Genetic Analysis of Callous-Unemotional Traits and Big Five Personality in Adolescence - Mann, Frank D. (J Abnorm Psychol, 2015)
Callous-unemotional (CU) traits, such as lacking empathy and emotional insensitivity, predict the onset, severity and persistence of antisocial behavior. CU traits are heritable, and genetic influences on CU traits contribute to antisocial behavior. This study examines genetic overlap between CU traits and general domains of personality. We measured CU traits using the Inventory of Callous and Unemotional Traits (ICU) and Big Five personality using the Big Five Inventory (BFI) in a sample of adolescent twins from the Texas Twin Project. Genetic influences on the Big Five personality dimensions could account for the entirety of genetic influences on CU traits. Item Response Theory results indicate that the ICU is better at detecting clinically relevant personality variation at lower extremes of personality trait continua, particularly low agreeableness and low conscientiousness. The proximate biological mechanisms that mediate genetic liabilities for CU traits remain an open question. The results of the current study suggest that understanding the development of normal personality may inform an understanding of the genetic underpinnings of callous and unemotional behavior.